(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Personal Financial Education of an individual is their level of understanding of their financial situation, impact of macro-economic changes, ability to plan in advance for critical life goals such as retirement, awareness of available financial products and channels, consult experts at the right time that enables them to be financially discipline and make informed decisions to achieve their life goals. An attempt has been made through this paper to understand millennials with reference to retirement planning and opportunities available for FinTechs to enable millennials to plan for their retirement both for accumulation and decumulation/distribution phase. Retirement planning should be presented as ‘Solution for life’ rather grouping it with other short-term financial goals.